Assessing the Effect of Socio-Scientific Inquiry-Based Learning on Socio-Scientific Decision-Making Skill among Senior High School Students - Maryam; Hadi Suwono (Postgraduate, University of Mataram, 2023)
The use of socio-scientific issues as a context in education is very important because education needs to include interdisciplinary and holistic learning. When dealing with socio-scientific issues, students are expected to be able to make competent decisions. This study was aimed to determine the effect of the Socio-scientific Inquiry-Based Learning (SSIBL) on students' socio-scientific decision-making skill. SSIBL is an inquiry-based learning model that places socio-scientific issues as learning contexts that need to be debated and solved through a series of inquiry processes. This study was a quasi-experimental with a non-equivalent control group design, conducted at senior high school MAN 2 Kota Bima, Indonesia. The target population consisting of all students of grade XI with a total of 254 students. Students of XI IPA 3, 4, 5, and 7 classes were chosen as samples through random sampling. Data were collected through pre-test and post-test of socio-scientific decision-making test, then analyzed using ANCOVA. The results showed that there were significant differences of socio-scientific decision-making between students in the experimental group and students in the control group. The research indicated that the SSIBL model has an effect on increasing the socio-scientific decision-making of students in grade XI MAN 2 Kota Bima.